-10n+24+24n=6n-24

Simple and best practice solution for -10n+24+24n=6n-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10n+24+24n=6n-24 equation:


Simplifying
-10n + 24 + 24n = 6n + -24

Reorder the terms:
24 + -10n + 24n = 6n + -24

Combine like terms: -10n + 24n = 14n
24 + 14n = 6n + -24

Reorder the terms:
24 + 14n = -24 + 6n

Solving
24 + 14n = -24 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
24 + 14n + -6n = -24 + 6n + -6n

Combine like terms: 14n + -6n = 8n
24 + 8n = -24 + 6n + -6n

Combine like terms: 6n + -6n = 0
24 + 8n = -24 + 0
24 + 8n = -24

Add '-24' to each side of the equation.
24 + -24 + 8n = -24 + -24

Combine like terms: 24 + -24 = 0
0 + 8n = -24 + -24
8n = -24 + -24

Combine like terms: -24 + -24 = -48
8n = -48

Divide each side by '8'.
n = -6

Simplifying
n = -6

See similar equations:

| 8x+40=-4x-28 | | M+-22=-50 | | 144k+132=144k+144 | | y=1/3(9)-3 | | 24+82=m-19+47 | | K+-21=42 | | -8x+-48=2x-128 | | -10k=1720 | | K+-36=36 | | 6-(6x+5x)=13 | | K+24=-36 | | 5.6+2.9-1.3=y+12.9-6.3 | | N+-15=-36 | | -2p=43 | | 5.2+x=31 | | X+-14=27 | | 5.2+x=41 | | 2x-5x-13=-3x+7-13 | | 3n^2+5n-2= | | (2x+1)(4x-1)=32 | | M+32=-40 | | H-12.6-4.5=4.8+19.6 | | M+12=-12 | | y=3x^4-6x^2+5 | | M+-6=-5 | | C+20=-10 | | (2x-9)(x+7)=0 | | 15+27-23=d-32 | | 92=2(x+x+4) | | 5[-3(3x+5)+3(5x-3)]= | | -5v+6=-19 | | 2y^2+x^2-4y-18=0 |

Equations solver categories